OPTIMAL DISIGN OF ENERGY SUPPLY NETS ON GRAPHS - Nikulshin, Vladimir; von Zedtwitz, Viktoria (International Journal of Computing, 2014)
In the design and operation of energy intensive systems, the possibility of improving the system’s efficiency is very important to explore. The main way of improving efficiency is through optimisation. This paper describes the application of exergy topological models and, in particular, the graph of thermoeconomical expenditure for thermoeconomical optimal design s of circled nets for energy supply (CNES). The questions of thermoeconomical optimisation of CNES, as well as suggested modelling algorithms, are illustrated in the numerical example of the optimisation of a energy supply system for a city with seven regions of energy consumption.